2011
DOI: 10.1021/cb200331g
|View full text |Cite
|
Sign up to set email alerts
|

Immune Interference in Mycobacterium tuberculosis Intracellular Iron Acquisition through Siderocalin Recognition of Carboxymycobactins

Abstract: The innate immune system, antibacterial protein Siderocalin (Scn) binds ferric carboxymycobactin (CMB) and also several catecholate siderophores. While the recognition of catecholates by Scn has been thoroughly investigated, the binding interactions of Scn with the full spectrum of CMB isoforms have not been studied. Here we show that Scn uses different binding modes for the limited subset of bound CMB isoforms, resulting in a range of binding affinities which are much weaker than other siderophore targets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The general recognition mechanism of Scn has been extensively studied and is well understood (22,24,(27)(28)(29)(30)(31)(32)(33). Ligands bind in the highly sculpted protein calyx, where the key interaction is through an aryl group binding in a snug pocket between the side chains of K125 and K134, with electrostatic and cation-π interactions to this ring and neighboring ones mediated by the side chains of R81, K124, and K134 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The general recognition mechanism of Scn has been extensively studied and is well understood (22,24,(27)(28)(29)(30)(31)(32)(33). Ligands bind in the highly sculpted protein calyx, where the key interaction is through an aryl group binding in a snug pocket between the side chains of K125 and K134, with electrostatic and cation-π interactions to this ring and neighboring ones mediated by the side chains of R81, K124, and K134 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although intrinsic tryptophan fluorescence quenching (FQ) has been used extensively to examine SCN binding (5, 8, 19), its susceptibility to spectroscopic interference prevents its use in chemically complex, urine-derived specimens. We therefore developed a different screening assay using a combined LC-DSF approach.…”
Section: Resultsmentioning
confidence: 99%
“…Human hosts have proteins that bind bacterial siderophores, preventing bacteria from scavenging host iron. One such human protein is lipocalin 2, which has been shown to bind the M. tuberculosis siderophore carboxymycobactin, potentially protecting the host against mycobacterial infection through iron sequestration (107,108). Three studies found that lipocalin 2 protein added to liquid cultures inhibited mycobacterial growth (52,109,110).…”
Section: Siderophores and Iron Sequestrationmentioning
confidence: 99%